Genetic components estimation of F1 population of cocoa (Theobromacacao L.) in drought stress condition. - Adinda Wuriandani; Sobir Sobir; Desta Wirnas; Agung Wahyu Susilo (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2019)
Drought stress is a major constraint in cocoa production. The use of drought tolerant clone is the most efficient tool to overcome drought problem in cocoa production. North Carolina II (NCII) mating-design was used to identify parental and progeny performance in drought stress. The crossing consisted of three female parent clones namely KW 516, Sulawesi 3, and TSH 858, while male parent clones were ICCRI 09 and Scavina 6 then produced 6 combinations crosses. Genotypes used were 11 genotypes consisted of 5 parent clones and 6 cross genotypes. Drought treatment was applied to cocoa seedlings at 6 weeks after sowing with 25% and 100% available water content. The plants were maintained without water for five days to modulate the drought intensity. Variables observed were stem diameter, root length, root volume, shoot fresh weight, root fresh weight, shoot dry weight, root dry weight, and root/shoot ratio characters at 16 weeks after sowing. Based on the estimated general combining ability (GCA) value, TSH 858 was the best female parent, while Scavina 6 was the best male parent. Based on the estimated specific combining ability (SCA) value Sulawesi 3 x ICCRI 09 and TSH 858 x Scavina 6 were the best crosses. Based on the estimation of its genetic components, characters of drought tolerance stress were affected by additive genes. The dominant gene only affected the root fresh weight and root/shoot ratio. Based on SSI values, TSH 858 and Sulawesi 3 clones were drought-resistant clones, ICCRI 09 was moderate clone, and KW 516 and Scavina 6 were susceptible. Some of the findings were in contrast with earlier study.